Manfred Beller y Joep Leerssen, Imagology:The Cultural Construction and Literary Representation of National Characters, Studia Imagologica Vol. 13, Amsterdam & New York: Rodopi, 2007 - Dahl, Julie M. (Limite. Revista de estudios portugueses y de la lusofonía, 2022)
recensión